A bifid mandibular condyle from a cremation grave from Paprotki Kolonia cemetery, Poland - Budziszewski, Adam; Karczewski, Maciej (Anthropological Review, 2024)
This study investigates the etiology of a bifid mandibular condyle found in a Bogaczewo culture cremation burial from the Paprotki Kolonia site 1. Using macroscopic analysis and CT imaging, we identified a sagittal separation of the mandibular condyle, suggesting a developmental origin. This represents the first known case of a bifid mandibular condyle from an Iron Age cremation context. Analytical potential is limited due to the preservation of only one condyle and the absence of teeth and temporobandibular surface, which do not allow us to assess the impact of this condition to the life quality of the individual.